A modified projective bi-inertial forward-backward splitting algorithm for detecting bone mineral density - Yothawut, Pentham; Peeyada, Pronpat; Liawrungrueang, Wongthawat; Cholamjiak, Watcharaporn (ScienceAsia : journal of the Science Society of Thailand, 2024)
Abstract only